Lung Function and Relevant Clinical Factors in Very Low Birth Weight Preterm Infants with Chronic Lung Disease: An Observational Study - I-Ling Chen; Hsiu-Lin Chen (Canadian Respiratory Journal)
Background. Chronic lung disease (CLD), most commonly seen in premature infants who required mechanical ventilation, is associated with functional consequences on lungs and respiratory morbidity. This study aimed to evaluate the lung function of premature infants before discharge and their relevant factors related to the lung function. Methods. Very low birth weight (VLBW) preterm infants, who required respiratory support soon after birth and were admitted to a hospital in Taiwan, were enrolled. Infants with a need for supplemental oxygen or positive-pressure ventilation support at the postmenstrual age (PMA) of 36 weeks were diagnosed with CLD. Lung function was examined once using EXHALYZER® D before infants were ready for discharge. Results. Forty-five VLBW preterm infants received the lung function test before discharge, 27 of whom were diagnosed with CLD. The gestational age (p=0.001) and birth weight (p<0.001) were smaller in the CLD group than in the no-CLD group. Furthermore, infants with CLD required a longer duration of respiratory support (p<0.001). The postnatal age and PMA were higher and body size was bigger in infants with CLD on lung function measurement. However, lung function was comparable between the groups. The functional residual capacity and tidal volume were associated with body size upon measuring lung function among all VLBW premature infants. FRC was positively correlated with the body length on measuring lung function in those with CLD. Conclusion. In our study, we showed FRC was positively related to the PMA and body length and tidal volume was positively correlated with the body weight and length on lung function measurement in VLBW preterm infants before discharge. Moreover, FRC was positively correlated with the body length on measuring lung function in those with CLD. The lung volume, ventilation, and respiratory mechanics on discharge were comparable between CLD and no-CLD groups.